US Sanctions and Foreign Lobbying of the US Government. (March 2023) - Peksen, Dursun; Peterson, Timothy M
Previous research has explored how US sanctions affect subsequent behavior by sanctioned states as well as third parties, with particular attention to whether states change the policies that led to US sanctions. In this paper, we argue that US sanctions also affect lobbying of the US government. States experiencing US sanctions over security and political issues will lobby the US government less than other states because this scenario suggests that lobbying is unlikely to influence US policies. States experiencing sanctions over economic issues, on the other hand, will lobby the US more as these targets would see a negotiated settlement as more feasible. We also maintain that third-party states that are similar to US sanction targets will lobby the US government more than dissimilar third parties, as lobbying in this scenario could be aimed at preempting future episodes of US sanctions—regardless of the issue that led to sanctions. We find support for our expectations in auto-regressive models spanning 1975–2005. Our findings suggest that sanctions in some cases lead states to find means other than policy concessions by which to satisfy US policy-makers.